PENGARUH GAYA KEPEMIMPINAN D DAN SUPERVISI AKADEMIK TERHADAP MOTIVASI KERJA GURU MADRASAH TSANAWIYAH SWASTA KABUPATEN PATI - Teguh Panatagama; Nurkolis Nurkolis; Akmal Akmal (Jurnal Manajemen Pendidikan (JMP), 2016)
The purpose of this study are: (1) to determine the influence of principal’s democratic leadership style towards work motivation teacher (2) to determine the influence of academic supervision towards work motivation teacher (3) to determine the influence of principal’s democratic leadership style and principal’s supervision academic towards work motivation of  private MTs’s teacher in sub-district Margoyoso Pati Regency.The population in this research are all teachers of private MTs in sub-district Margoyoso Pati Regency they are  186 peoples, with a sample of 110 peoples by using proportional random sampling technique. Data collection method were used a questionnaire. The analysis of the data was used  descriptive analysis, test requirements and test hypotheses include simple linear regression used SPSS for Window.The results of this research is  the average acquisition score of work motivation of  teacher 134,51  categorized  medium category, the average acquisition score of principal’s democratic leadership style 110,35 categorized  democratic enough category, and the average acquisition score of principal’s supervision academic 114,26 categorized  good enough category. The test results of the research data are obtained prerequisite normal distribution of data, homogeneous, linear, and not multikolinier. The hypothesis tests are found: (1) there is a positive influence principal’s democratic leadership style to work motivation of  teacher that is expressed by the equation Y = –2,783 + 1,244X1; the strength of correlation is 0,808 with a contribution about 0,653 or 65,3%, (2) there is a positive influence in principal’s supervision academic to work motivation of  teacher that is expressed by the equation Y = –2,292 + 1,197X2; the strength of correlation is 0,809 with a contribution about 0,654 or 65,4% and  (3) there is a positive influence on principal’s democratic leadership style and principal’s supervision academic together towards work motivation of  teacher expressed by the equation Y = –15,376 + 0,680X1 + 0,658X2; the strength of correlation is 0,846 with a contribution about 0,716 or 71,6%.